Three-Phase Transmission Line Fault Detection and Its Location - Maurya, Shailesh Kumar (Stallion Journal for Multidisciplinary Associated Research Studies, 2024)
Nowadays, the per capita consumption of Electrical Energy is a parameter of any country's Development. In India, we are working on improving Transmission Line Efficiency by using semiconductor drives and information technology to increase the per capita electrical energy consumption. This paper has the proposed model for three-phase fault detection & its location. In transmission lines, there are two types of faults: (i) symmetrical fault and (ii) unsymmetrical fault. Generally, the B Phase follows the kinds of faults in transmission line Single Line to Ground Fault Line-to-Line Fault Double Line to Ground Fault This article used an IoT application to detect faults and their locations.